Internationalization and innovation orientation as factors of employee learning and development adaptation during Covid-19: Evidence from Polish SMEs - Agnieszka Żur; Agnieszka Wałęga (Entrepreneurial Business and Economics Review (EBER), 2023)
Objective: With no or very few studies investigating employee learning and development adaptation in SMEs during Covid we address an important research gap. The driving aim of this study is to test whether SMEs with a higher level of internationalization and innovation orientation were able to adapt their training and development activities quicker and better than others. Research Design & Methods: We test the hypothesized relationships on a sample of 214 Polish SMEs. Data was collected using the CATI method. Ordered probit model and logit model were employed to analyse the data. Findings: While the results clearly indicate that innovation orientation had an impact on the adaptation of training and development for Polish SMEs during first year of Covid Pandemic, internationalization did not exhibit any significant impact on the amount of trainings conducted during first year of Covid. However, the existence of prior experience with online technologies may have moderated the relationship between internationalization and adaptation of learning and development. Implications & Recommendations: To become quick adapters SMEs should develop an innovation orientation, implement online learning practices and foster mutual learning within the organization, as well as take every opportunity to learn from external partners. Contribution & Value Added: With this study we contribute to the body of knowledge investigating SME adaptation during Covid. This research implies that innovation orientation can positively influence how firms adapt their training and development in times of crisis. This pioneering contribution is an important piece of the puzzle of what might determine the competitive advantage of some SMEs over others in years to come.
Keywords: L20; O30; 330; SMEs; Covid pandemic; adaptation; internationalization; innovation performance